2021
DOI: 10.1007/s40519-021-01338-7
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the impact of carer interventions on outcomes for patients with eating disorders

Abstract: Purpose Eating disorder (ED) prevalence and illness severity is rapidly increasing. The complicated interplay of factors contributing to the maintenance of EDs, including family/carer influences, highlights the importance of carer interventions within ED treatment. Carer interventions demonstrate positive outcomes for carers themselves, though are also hypothesised to benefit the patient indirectly. A systematic review was conducted to greater understand the impact of carer interventions on ED pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…Similar to the majority of supporters in Hannah et al.’s (2021) review, most supporters who opted into our workshops and completed the outcome measures were white British, female parents. Next time, we could work more closely with individual therapists within the service to identify more cases where it might be useful to involve more males, friends, siblings, children and partners.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Similar to the majority of supporters in Hannah et al.’s (2021) review, most supporters who opted into our workshops and completed the outcome measures were white British, female parents. Next time, we could work more closely with individual therapists within the service to identify more cases where it might be useful to involve more males, friends, siblings, children and partners.…”
Section: Discussionmentioning
confidence: 74%
“…A systematic review and synthesis of 28 studies on the impact of interventions for supporters of loved ones with EDs found supporters benefited from working with peers in a group setting and felt more equipped to help manage the disorder (Hannah et al., 2021). This has led to many services, including our own, delivering skills‐based workshops for supporters as part of usual care (Pépin & King, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of parents believed that these vPLPSGs should be widely available, indicating that they are a pivotal part of the continuum of care in pediatric EDs. Currently, there is a lack of support for parents despite a stated need for more peer support, as it assists them in being able to manage their child’s ED [ 36 ]. Parents are also burdened by long waiting lists at various stages of pediatric ED care and face challenges in accessing ED services, harbouring emotions of guilt and self-blame [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research on eating disorders and risky eating behaviors (REB) have increased over time, due to their prevalence and health consequences, mainly in the young population 1,17 . According to the National Health and Nutrition Survey concerns about gaining weight, losing control over eating and overeating were the most frequent REB in the Mexican adolescent population.…”
Section: Discussionmentioning
confidence: 99%